HUBUNGAN BONITA DENGAN KELAS KESESUAIAN LAHAN (KKL) HUTAN TANAMAN JATI - Beny H; Pamungkas B.P; Heru Dwi Riyanto (JURNAL LITBANG PROVINSI JAWA TENGAH, 2020)
The fast way knowing the site quality by bonita approach, is only for well managed forest. Land suitability is fixed level of land width for particular utilization, this land suitability could be valuated at present condition or after improving action. This research conducted on Forest within work area of BKPH Pasarsore and Cabak, KPH Cepu. The observation site used as sample plot based on aged class and bonita, each them was three times replicated. Parameters observed consist of land resource aspect and stand aspect. The data analyze of ISDL’s outcome was Land Suitability Class in each observation plot, then it could be used as land/site evaluation, then classified into three classes, such as: S1 (very suitable), S2 (suitable) and S3 (marginal suitable). To make the equality between land classification and bonita, thus the bonita also classified into three class, such as: bonita 3 as good enough for teak growth, bonita 3.5 as good for teak growth and bonita 4-5 as very good for teak growth. The equality result in generally, between bonita version and land suitability class version, from totally 77 observation plots, criteria/class S1 (very suitable) occupy 64%, S2 (suitable) 25% dan S3 (marginal suitable) 11%. From each bonita, on bonita 3 : S1 occupy 50%, S2 44% dan S3 6%; on bonita 3,5 : S1 occupy 65%, S2 15% dan S3 20%; on bonita 4 : S1 occupy 64%, S2 24% dan S3 12%; on bonita 4,5-5 : S1 occupy 88%, S2 12% dan S3 0%.